Using generalizability analysis to estimate parameters for anatomy assessments: A multi‐institutional study. Issue 2 (26th July 2016) - Byram, Jessica N.; Seifert, Mark F.; Brooks, William S.; Fraser‐Cotlin, Laura; Thorp, Laura E.; Williams, James M.; Wilson, Adam B.
Abstract : With integrated curricula and multidisciplinary assessments becoming more prevalent in medical education, there is a continued need for educational research to explore the advantages, consequences, and challenges of integration practices. This retrospective analysis investigated the number of items needed to reliably assess anatomical knowledge in the context of gross anatomy and histology. A generalizability analysis was conducted on gross anatomy and histology written and practical examination items that were administered in a discipline‐based format at Indiana University School of Medicine and in an integrated fashion at the University of Alabama School of Medicine and Rush University Medical College. Examination items were analyzed using a partially nested design s × ( i : o ) in which items were nested within occasions ( i:o ) and crossed with students ( s ). A reliability standard of 0.80 was used to determine the minimum number of items needed across examinations (occasions) to make reliable and informed decisions about students' competence in anatomical knowledge. Decision study plots are presented to demonstrate how the number of items per examination influences the reliability of each administered assessment. Using the example of a curriculum that assesses gross anatomy knowledge over five summative written and practical examinations, the results of the decision study estimated that 30 and 25 items would be needed on each written and practical examination to reach a reliability of 0.80, respectively. This study is particularly relevant to educators who may question whether the amount of anatomy content assessed in multidisciplinary evaluations is sufficient for making judgments about the anatomical aptitude of students. Anat Sci Educ 10: 109–119. © 2016 American Association of Anatomists.